Portrait of Friendship among Catholic Youth: A Preparatory Step toward Catholic Marriage at St. Fransiskus Asisi Laverna Gunungsitoli and Kristus Gembala Baik Parishes - Mendrofa, Kristiana; Ola, Dominikus Doni; Obe, Alexius Poto; Masong, Kenneth C.; Gea, Maniati (International Journal of Artificial Intelligence Research, 2025)
This study analyzes friendship among Catholic Youth (Orang Muda Katolik—OMK in Bahasa Indonesia) as a crucial factor in forming emotional, spiritual, and social readiness for Catholic marriage. The qualitative study was conducted in two parishes—St. Fransiskus Asisi Laverna Gunungsitoli and Kristus Gembala Baik—using in-depth interviews, participant observation, and document analysis. The findings indicate that healthy, value-based friendships within the Catholic Youth community contribute significantly to fostering responsible relationships as a foundation for marriage. Key aspects supporting relational maturity include trust, open communication, mutual respect, and active participation in religious activities. These factors reinforce the psychosocial aspects necessary for building stable and meaningful relationships before entering into marriage. This study highlights the need for a more systematic approach by the Church in integrating friendship development into premarital preparation programs, particularly in pastoral care for Catholic youth. Thus, friendship is not merely a social experience but serves as a pathway toward a holy and committed family life. Further research is encouraged to explore how faith-based education can strengthen friendships as a foundation for mature relationships.